(untitled) - Rockwell, Stephen J. (Boston, 2001)
A brief introduction to American Government, this text has three main advantages over other books in this market: innovative and flexible teacher tools; novel chapter progression and adaptable topics; and creative resources for students. The text opens with a discussion of the media first, then follows the themes of competition and compromise throughout. By delving first into the media, the text draws students into a discussion of government as they experience it on an everyday basis. Once the students' interests are piqued, the more traditional topics of the constitution and institutions of government are covered. The competition and compromise theme reflects the authors' approach: how the Madisonian system is played out in every institution of government and in every political process. Now packaged with PowerWeb, a dynamic course-specific rather than book-specific supplement that engages your students in three levels of resource materials and provides a true avenue to extending learning about a subject, American Government is a necessity in any American Government course.
Keywords: Xã hội dân chủ,Democracy; Nước Mỹ,United States